2014
DOI: 10.4238/2014.november.27.6
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of HSF3 and HSP70 mRNA expression in the tissues of two chicken breeds during acute heat stress

Abstract: ABSTRACT. This study aimed to estimate changes in HSF3 and HSP70 mRNA expression in stress-sensitive tissues of 2 chicken breeds during acute heat stress. Lingshan chickens (LSC) and White Recessive Rock (WRR) (24 chickens of each breed) were randomly divided into 4 groups (0, 2, 3, and 6 h of heat treatment). With increasing heat treatment time, both HSF3 and HSP70 expression first declined and then showed a significant increase in both breeds. However, HSP70 expression decreased in the heart following 6 h of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…In contrast to the results in jejunum and ileum, no heat stress-related alterations in HSP70 and HSP90 mRNA expression were observed in duodenum and colon, indicating again differences in the susceptibility of the individual parts of the intestines. These findings are in line with a study Zhang et al, [ 43 ] in which differences in the mRNA expression of HSF3 and HSP70 between two chicken breeds and tissue-specific differences during heat treatment are described.…”
Section: Discussionsupporting
confidence: 92%
“…In contrast to the results in jejunum and ileum, no heat stress-related alterations in HSP70 and HSP90 mRNA expression were observed in duodenum and colon, indicating again differences in the susceptibility of the individual parts of the intestines. These findings are in line with a study Zhang et al, [ 43 ] in which differences in the mRNA expression of HSF3 and HSP70 between two chicken breeds and tissue-specific differences during heat treatment are described.…”
Section: Discussionsupporting
confidence: 92%
“…Many studies have demonstrated the damage or injury of the heart, liver, and brain tissues, as well as and angiocarpy in chickens and rats under HS (Zhang et al, 2014;Quinn et al, 2015;Ito et al, 2015). Moreover, AHS triggers the expression of heat stress-related genes, such as HSP70, HSP70s, TLR2 and TLR4 (Ju et al, 2014;Zhang et al, 2014;Richter et al, 2015;Zhang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It well known that poultry species, particularly broiler chickens, are more sensitive to high environmental temperatures and humidity levels than other domestic animals because of their feather cover, lack of sudoriferous glands, and fast growth rate (Piestun et al, 2013;Di et al, 2015). When the environmental temperature exceeds the optimal temperature range, broilers show signs of heat stress, including rise in body temperature, reduced feed intake, poor reproductive and growth performance, immunosuppression, and increased mortality (Kamboh et al, 2013;Zhao et al, 2013;Zhang et al, 2014;Lasagna et al, 2015;Li et al, 2015;Sun et al, 2015). Many studies have demonstrated the damage or injury of the heart, liver, and brain tissues, as well as and angiocarpy in chickens and rats under HS (Zhang et al, 2014;Quinn et al, 2015;Ito et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations